Natural regeneration dynamics of secondary forests in Bragança, Pará, Brazil - Rayol, Breno Pinto; Silva, Manoela Ferreira Fernandes da; Alvino, Fabrízia de Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The objective was to assess modes the dynamic of the floristic composition of natural regeneration in areas of secondary forest with different ages of sucession localized in municipality of Bragança, Pará. Three areas with 20, 30 and 30 years of sucession were chosen. Three size classes were established in order to stratify the specimens under study: class 1 – specimens ranging from 30 cm to 1,5 m in height; class 2 – specimens more than 1,5 m tall, but with DBH < 2,5 cm; and class 3 – specimens with 2,5 cm £ DBH < 5 cm. The families with larger representative in these two areas were Leguminosae and Myrtaceae. The genera with larger occurrence were Inga and Myrcia . Species like Phyllanthus nobilis, Gustavia augusta, Abarema jupunba, Myrcia paivae, Ouratea castaneaefolia, Myrciaria tenella and Myrcia bracteata occurred in the three sampling and in all the size classes.
Keywords: Natural regeneration; Secondary forest; Forest dynamic